Low stress epoxy encapsulation material and planar waveguide optical splitter

CN122647852BActive Publication Date: 2026-10-30ZHEJIANG KEXU PHOTOELECTRIC TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611163090.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-30
Estimated Expiration
2046-08-03

AI Technical Summary

Technical Problem

[0004]然而,传统低应力多依赖添加柔性助剂、稀释剂实现应力降低,难以兼顾低应力特性与机械结构强度

Benefits of technology

1、本发明通过刚性环氧树脂与柔性环氧树脂复配构建刚柔复合基体,并结合自制交联改性剂调控体系交联密度,改善了传统材料难以兼顾低应力与机械强度的问题。采用刚柔树脂复配的方式,在分子层面形成互嵌式复合骨架结构,刚性树脂固化形成稳定的三维交联网络,为封装结构提供基础支撑刚度与抗机械形变能力,柔性树脂长链段均匀分布于交联网格间隙。配合改性剂封端改性调控交联程度,可有效缓解固化过程中的分子堆砌收缩效应,适度释放固化应力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of optical communication materials, and more particularly to a low-stress epoxy packaging material and a planar waveguide optical branching device, which is composed of an epoxy matrix resin, a crosslinking modifier, a filler, an antioxidant and a silane coupling agent by weight parts. The crosslinking modifier is prepared by melting 1,6-dimalimide hexane, adding furfurylamine dropwise and reacting under insulation to obtain a prepolymer melt, and then adding a difunctional epoxy diluent to cap after cooling. The present application uses rigid and flexible epoxy resin to build a composite matrix, and cooperates with a self-made dynamic crosslinking modifier and a silane coupling agent to modify the interface and build a hybrid crosslinking network, so as to effectively balance the low stress and high toughness performance of the material, reduce the curing residual stress and optical loss, and adapt to the long-term stable packaging requirements of precision optoelectronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical communication materials technology, and in particular to a low-stress epoxy encapsulation material and a planar waveguide optical splitter. Background Technology

[0002] Optical splitters are core passive devices in optical communication networks, primarily used to split a single optical signal into multiple optical signals. They are widely used in fiber-to-the-home, data centers, and industrial optical networks. With the large-scale deployment of 5G-A and gigabit optical networks, the demand for optical splitters continues to grow. The performance and environmental friendliness of their packaging materials directly affect the lifespan, maintenance costs, and environmental impact of optical splitters. Epoxy resin materials, due to their excellent insulation, adhesion, optical transmittance, and molding processability, as well as their controllable cost and suitability for mass production, have long been widely used in the packaging process of planar waveguide optical splitters. A qualified epoxy packaging structure can effectively protect precision waveguide chips and fiber coupling interfaces, isolating them from external moisture, dust, mechanical forces, and temperature changes, fixing the optical path coupling structure, avoiding problems such as optical path misalignment and coupling failure, and ensuring the stability of optical signal transmission.

[0003] The invention patent with publication number CN101054508A discloses a composite epoxy electronic packaging material and its preparation method, including epoxy resin, epoxy alkyl organosilicon coupling agent, inorganic silica filler, naphthalene, formaldehyde condensate of naphthalene, reactive phosphorus-containing flame retardant, curing agent, and aminoalkyl organosilicon coupling agent. This composite epoxy electronic packaging material has the advantages of high heat resistance, low water absorption, and good environmental protection and flame retardancy.

[0004] However, traditional low-stress methods often rely on adding flexible additives and diluents to reduce stress, making it difficult to balance low-stress characteristics with mechanical structural strength. While excessively increasing the flexible component can alleviate curing shrinkage stress, it significantly reduces the rigidity and structural support stability of the cured epoxy resin, resulting in insufficient vibration and compression resistance of the encapsulated device. Furthermore, existing low-stress epoxy encapsulation materials exhibit poor curing cross-linking network regularity, leading to significant volume shrinkage during curing. This results in prominent residual internal stress after device encapsulation, and the thermal expansion coefficients of conventional materials are poorly matched with those of the waveguide chip substrate, easily generating continuous alternating thermal stress under complex operating conditions such as high and low temperature fluctuations. Long-term stress can cause problems such as refractive index distortion of the waveguide chip, micro-shifting of the optical path, and misalignment of the fiber coupling interface, directly increasing the insertion loss of the optical splitter and deteriorating the splitting uniformity, severely affecting the accuracy and stability of optical signal transmission. Moreover, continuous stress accumulation can easily cause hidden defects such as microcracks and interface delamination in the encapsulation system, resulting in poor environmental reliability and a significantly shortened service life, making it unsuitable for the long-term stable operation requirements of high-end optical communication devices. Summary of the Invention

[0005] To address the problems mentioned in the background section, this invention provides a low-stress epoxy encapsulation material and a planar waveguide optical splitter.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A low-stress, removable epoxy encapsulation material comprises the following raw material components by weight: 60-70 parts epoxy resin, 25-35 parts crosslinking modifier, 3-6 parts filler, 1.5-3.0 parts antioxidant, and 0.5-1.0 parts silane coupling agent; The crosslinking modifier is specifically prepared through the following steps: S1. Melt 1,6-dimaleimide hexane, add furfurylamine dropwise, and continue the reaction at the same temperature after the dropwise addition is completed to obtain the prepolymer melt; S2. Cool the prepolymer melt, then add a bifunctional epoxy diluent for end-capping, and control the reaction system conditions to obtain the crosslinking modifier.

[0007] Furthermore, the epoxy resin is composed of flexible epoxy resin and rigid epoxy resin, with a mass ratio of (1-2):1. The flexible epoxy resin is selected from one or more of polypropylene glycol diglycidyl ether, butylene glycol diglycidyl ether, and neopentyl glycol diglycidyl ether; The rigid epoxy resin is selected from one or more of bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, and o-cresol epoxy resin.

[0008] Furthermore, the filler is selected from one or more of silica, alumina, and boron nitride, and the particle size of the filler is 0.5-10μm; the moisture content of the filler is ≤0.1%, and the filler is pre-treated by drying at 110-130℃ for 2-4h before use.

[0009] Furthermore, the antioxidant is selected from one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1010), octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1076), and 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (antioxidant 330).

[0010] Furthermore, the silane coupling agent is selected from one or more of γ-glycidoxypropyltrimethoxysilane (KH-560), γ-aminopropyltriethoxysilane (KH-550), and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH-792).

[0011] Furthermore, in step S1, the melting temperature is 130-140℃, the dropping rate of furfurylamine is 1-2 drops per second, the dropping process lasts for 45-60 minutes, and the stirring is continuous during the dropping process; after the dropping is completed, the reaction is continued at this temperature range for 2.0-3.0 hours, and the entire reaction is carried out under the protection of an inert gas. The mass ratio of 1,6-dimaleimide hexane to furfurylamine is 1:(1.30-1.59).

[0012] Furthermore, in step S2, after the prepolymer melt is cooled to 65-75°C, a bifunctional epoxy diluent is added; The bifunctional epoxy diluent is selected from one or more of neopentyl glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, and polyethylene glycol diglycidyl ether, and its addition amount is 5-15% of the mass of 1,6-dimaleimide hexane.

[0013] In step S2, after adding the bifunctional epoxy diluent, the mixture is kept at a constant temperature and stirred for 40-80 minutes at a stirring speed of 200-400 r / min.

[0014] Furthermore, step S2 also includes adding a catalyst, which is selected from one or more of benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 2-methylimidazole, and the amount added is 0.05-0.2% of the melt weight of the prepolymer; the reaction system is sealed and protected from light throughout the process.

[0015] Furthermore, it is prepared by the following steps: The epoxy resin, filler, and silane coupling agent are mixed evenly at 80-100℃ and then subjected to vacuum degassing. Subsequently, a crosslinking modifier heated to 60-70℃ is added and blended to form a homogeneous adhesive solution. This solution is then injected into a preheated mold and subjected to pre-curing at 80℃, curing at 100℃, and post-curing at 120℃ to complete the crosslinking process. After cooling, the product is obtained.

[0016] The mixing speed is 400-600 r / min, and the mixing time is 30-50 min; the vacuum degassing degree is (-0.08)-(-0.1) MPa, and the degassing time is 15-25 min; the mold preheating temperature is 70-80℃; the pre-curing time at 80℃ is 1-2 h, the curing time at 100℃ is 2-3 h, and the post-curing time at 120℃ is 1-1.5 h, and the material is discharged after natural cooling to room temperature.

[0017] According to another aspect of the present invention, a planar waveguide optical splitter is provided, comprising an optical waveguide chip and an encapsulation layer covering the optical waveguide chip, wherein the encapsulation layer is made of the aforementioned low-stress, removable epoxy encapsulation material. The optical waveguide chip is a silicon-based or quartz-based planar optical waveguide chip, and the encapsulation layer has a thickness of 80-200 μm, completely covering the optical path area and fiber coupling interface of the optical waveguide chip.

[0018] The beneficial effects of this invention are: 1. This invention constructs a rigid-flexible composite matrix by compounding rigid and flexible epoxy resins, and uses a self-made crosslinking modifier to regulate the crosslinking density of the system, thus improving the problem of traditional materials struggling to balance low stress and mechanical strength. By using a rigid-flexible resin compounding method, an interlocking composite framework structure is formed at the molecular level. The rigid resin cures to form a stable three-dimensional crosslinked network, providing basic support rigidity and resistance to mechanical deformation for the encapsulation structure. The long chain segments of the flexible resin are uniformly distributed in the gaps between the crosslinked network. The use of a modifier to end-cap and regulate the degree of crosslinking effectively alleviates the molecular stacking shrinkage effect during curing and appropriately releases curing stress.

[0019] 2. In the technical solution of this invention, the crosslinking modifier first undergoes a cycloaddition reaction with furfurylamine via the long-chain alkyl backbone of 1,6-dimaleimide hexane and the terminal maleimide active structure, generating a prepolymer molecule with a furan cycloaddition structure. This gives the prepolymer backbone a flexible long-chain structure, while introducing thermally reversible cycloaddition bonding sites into the molecular network. Then, the active end groups of the prepolymer are capped with a bifunctional epoxy diluent, appropriately passivating the highly active crosslinking sites on the prepolymer surface. Finally, a composite molecular structure is formed, possessing a flexible long-chain backbone, reversible dynamic bonding sites, and controllable epoxy reactivity. Overall, it exhibits a multi-level structural characteristic of a long-chain flexible backbone, controllable end activity, and the presence of temperature-sensitive reversible bonds within the molecule. The modifier's long-chain flexible framework can interpenetrate within the epoxy matrix crosslinking network, effectively increasing the free volume of the crosslinking network, alleviating the volume shrinkage caused by the tight stacking of molecular chains during curing, moderately reducing the overall crosslinking density of the system, and weakening residual stress after curing. This allows the material to achieve low-stress characteristics while maintaining the rigidity of the basic structure, avoiding the stress concentration problem of traditional high-crosslinking-density epoxy systems. Secondly, the thermally reversible cycloaddition structure introduced into the modifier molecule can uniformly participate in the overall crosslinking molding, stably implanting dynamic covalent bond sites within the system, forming a hybrid crosslinking structure with the permanent crosslinking network of the epoxy matrix. This provides the encapsulation material with controllable temperature-sensitive decrosslinking capability, enabling the material to have disassembled and repairable application characteristics. Simultaneously, the molecular activity after end-capping modification with the bifunctional epoxy diluent is more balanced, improving the compatibility between the modifier and the epoxy matrix, promoting uniform crosslinking reaction, enhancing the structural regularity of the overall crosslinking network, and reducing localized over-crosslinking and structural defects during curing. During the molding and service process, the rigid-flexible cross-linked structure constructed by the modifier can help optimize the thermal deformation characteristics of the system, coordinate the thermal matching between the packaging material and the optical waveguide chip, weaken the accumulation of thermal stress under high and low temperature alternating conditions, and help improve the long-term stability and environmental adaptability of the packaging structure. Detailed Implementation

[0020] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] In the following examples and comparative examples, the flexible epoxy resins of polypropylene glycol diglycidyl ether, butanediol diglycidyl ether, and neopentyl glycol diglycidyl ether, the rigid epoxy resins of bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, and o-cresylaldehyde epoxy resin, as well as the difunctional epoxy diglycidyl ether, 1,4-butanediol diglycidyl ether, and polyethylene glycol diglycidyl ether difunctional epoxy diluents, were all industrial grade; 1,6-dimaleimide hexane (CAS No.: 4856-87-5) and furfurylamine (CAS No.: 617-89-0) were both analytical grade; benzyl dimethylamine... Catalysts (CAS No.: 103-83-3), 2,4,6-tris(dimethylaminomethyl)phenol (CAS No.: 90-72-2), and 2-methylimidazole (CAS No.: 693-98-1) are all analytical grade; antioxidants 1010, 1076, and 330 are all industrial grade; γ-glycidoxypropyltrimethoxysilane (KH-560), γ-aminopropyltriethoxysilane (KH-550), and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH-792) silane coupling agents are all industrial grade.

[0022] Example 1 This embodiment provides a low-stress, removable epoxy encapsulation material, with the following specific raw material feed weights: 60g epoxy resin, 25g crosslinking modifier, 3g silica filler, 1.5g antioxidant 1010, and 0.5g KH-560 silane coupling agent.

[0023] The epoxy resin is composed of 30g of butanediol diglycidyl ether and 30g of bisphenol A diglycidyl ether. The filler particle size is 0.5μm. It is pretreated by drying at 110℃ for 4h before use.

[0024] The crosslinking modifier is prepared using the following steps: S1, 10g of 1,6-dimaleimide hexane is heated to 130℃ to melt, and 13.0g of furfurylamine is added dropwise at a rate of 1-2 drops per second for 45 minutes under an inert gas protection environment. The addition is continuously stirred during the addition process, and the reaction is maintained at the temperature for 2.0h after the addition is completed to obtain the prepolymer melt; S2, the prepolymer melt is cooled to 65℃, and 0.5g of 1,4-butanediol diglycidyl ether and 0.0115g of 2-methylimidazole catalyst are added. The reaction is carried out under sealed and light-proof conditions with stirring at 200r / min for 40 minutes to obtain the crosslinking modifier.

[0025] The preparation method of the epoxy encapsulation material in this embodiment is as follows: 60g of epoxy resin, 3g of pretreated silica filler and 0.5g of KH-560 silane coupling agent are placed in a stirring device and stirred at 400r / min for 30min at 80℃, followed by degassing at -0.08MPa vacuum for 15min; 25g of the prepared crosslinking modifier is heated to 60℃ and added to the mixed adhesive solution to form a homogeneous adhesive solution; the adhesive solution is injected into a mold preheated at 70℃, and then pre-cured at 80℃ for 1h, cured at 100℃ for 2h, and post-cured at 120℃ for 1h in sequence. After naturally cooling to room temperature, the material is discharged to obtain a low-stress, removable epoxy encapsulation material.

[0026] Example 2 This embodiment provides a low-stress, removable epoxy encapsulation material, with the following specific raw material feed weights: 65g epoxy resin, 30g crosslinking modifier, 4.5g alumina filler, 2.2g antioxidant 1076, and 0.75g KH-550 silane coupling agent.

[0027] The epoxy resin is composed of 39g of polypropylene glycol diglycidyl ether and 26g of bisphenol F diglycidyl ether. The filler particle size is 5μm. Before use, it is pretreated by drying at 120℃ for 3h. The moisture content of the filler is controlled within 0.1%.

[0028] The crosslinking modifier was prepared using the following steps: S1, 10g of 1,6-dimaleimide hexane was heated to 135℃ to melt. Under an inert gas environment, 14.5g of furfurylamine was added dropwise at a rate of 1-2 drops per second for 50 minutes, with continuous stirring during the addition process. After the addition was completed, the reaction was maintained at the temperature for 2.5 hours to obtain the prepolymer melt; S2, the prepolymer melt was cooled to 70℃, and 1.0g of neopentyl glycol diglycidyl ether and 0.0294g of benzyl dimethylamine catalyst were added. Under a sealed and light-protected condition, the reaction was maintained at 300r / min with stirring for 60 minutes to obtain the crosslinking modifier.

[0029] The preparation method of the epoxy encapsulation material in this embodiment is as follows: 65g of epoxy resin, 4.5g of pretreated alumina filler and 0.75g of KH-550 silane coupling agent are placed in a stirring device and stirred at 500r / min for 40min at 90℃. Then, the mixture is degassed under a vacuum of -0.09MPa for 20min. 30g of the prepared crosslinking modifier is heated to 65℃ and added to the mixed adhesive solution to form a homogeneous adhesive solution. The adhesive solution is injected into a mold preheated at 75℃ and then pre-cured at 80℃ for 1.5h, cured at 100℃ for 2.5h, and post-cured at 120℃ for 1.2h. After naturally cooling to room temperature, the material is discharged to obtain a low-stress, removable epoxy encapsulation material.

[0030] Example 3 This embodiment provides a low-stress, removable epoxy encapsulation material, with the following specific raw material feed weights: 70g epoxy resin, 35g crosslinking modifier, 6g boron nitride filler, 3.0g antioxidant 330, and 1.0g KH-792 silane coupling agent.

[0031] The epoxy resin is composed of 46.67g of neopentyl glycol diglycidyl ether and 23.33g of o-cresol epoxy resin. The filler particle size is 10μm. Before use, it is pretreated by drying at 130℃ for 2h. The moisture content of the filler is controlled within 0.1%.

[0032] The crosslinking modifier was prepared using the following steps: S1, 10g of 1,6-dimaleimide hexane was heated to 140℃ to melt, and 15.9g of furfurylamine was added dropwise at a rate of 1-2 drops per second for 60 minutes under an inert gas atmosphere. The addition was carried out with continuous stirring. After the addition was completed, the reaction was kept at the temperature for 3.0 hours to obtain the prepolymer melt; S2, the prepolymer melt was cooled to 75℃, and 1.5g of polyethylene glycol diglycidyl ether was added, along with 0.0518g of 2,4,6-tris(dimethylaminomethyl)phenol catalyst. The reaction was carried out under sealed and light-protected conditions with stirring at 400r / min for 80 minutes to obtain the crosslinking modifier.

[0033] The preparation method of the epoxy encapsulation material in this embodiment is as follows: 70g of epoxy resin, 6g of pretreated boron nitride filler and 1.0g of KH-792 silane coupling agent are placed in a stirring device and stirred at 600r / min for 50min at 100℃, followed by degassing at -0.1MPa vacuum for 25min; 35g of the prepared crosslinking modifier is heated to 70℃ and added to the mixed adhesive solution to form a homogeneous adhesive solution; the adhesive solution is injected into a mold preheated to 80℃, and then pre-cured at 80℃ for 2h, cured at 100℃ for 3h, and post-cured at 120℃ for 1.5h in sequence. After naturally cooling to room temperature, the material is discharged to obtain a low-stress, removable epoxy encapsulation material.

[0034] Example 4 This embodiment provides a low-stress, removable epoxy encapsulation material, with the following specific raw material feed weights: 68g epoxy resin, 32g crosslinking modifier, 4g silica filler, 2.0g antioxidant 1010, and 0.8g KH-560 silane coupling agent.

[0035] The epoxy resin is composed of 36g of polypropylene glycol diglycidyl ether and 32g of bisphenol A diglycidyl ether. The filler particle size is 3μm. Before use, it is pretreated by drying at 120℃ for 3h. The moisture content of the filler is controlled within 0.1%.

[0036] The crosslinking modifier was prepared using the following steps: S1, 10g of 1,6-dimaleimide hexane was heated to 138℃ to melt, and 14.0g of furfurylamine was added dropwise at a rate of 1-2 drops per second for 55 minutes under an inert gas atmosphere. The addition was carried out with continuous stirring. After the addition was completed, the reaction was kept at the temperature for 2.8 hours to obtain a prepolymer melt; S2, the prepolymer melt was cooled to 72℃, and 1.2g of polyethylene glycol diglycidyl ether and 0.036g of 2-methylimidazole catalyst were added. The reaction was carried out under sealed and light-protected conditions with stirring at 350r / min for 70 minutes to obtain 32g of crosslinking modifier.

[0037] The preparation method of the epoxy encapsulation material in this embodiment is as follows: 68g of epoxy resin, 4g of pretreated silica filler and 0.8g of KH-560 silane coupling agent are placed in a stirring device and stirred at 550r / min for 45min at 95℃. Then, the mixture is degassed under a vacuum of -0.09MPa for 22min. 32g of the prepared crosslinking modifier is heated to 68℃ and added to the mixed adhesive solution to form a homogeneous adhesive solution. The adhesive solution is injected into a mold preheated to 78℃ and then pre-cured at 80℃ for 1.8h, cured at 100℃ for 2.8h, and post-cured at 120℃ for 1.3h. After naturally cooling to room temperature, the material is discharged to obtain a low-stress, removable epoxy encapsulation material.

[0038] Comparative Example 1 The comparative example is completely consistent with the raw material dosage and preparation process of Example 1. The difference is that no crosslinking modifier is added, and the other raw material components, ratios and all preparation and curing process parameters are consistent with those of Example 1.

[0039] Comparative Example 2 The comparative example is completely consistent with Example 2 in terms of raw material dosage and preparation process. The difference is that the silane coupling agent KH-550 is not added. The other raw material components, ratios and all preparation and curing process parameters are consistent with Example 2.

[0040] Comparative Example 3 The comparative example is completely consistent with Example 3 in terms of raw material dosage and preparation process. The difference is that 1,6-dimaleimide hexane is not added during the preparation of the crosslinking modifier. The other raw material components, ratios and all preparation and curing process parameters are consistent with those of Example 3.

[0041] Comparative Example 4 The raw material dosage and preparation process of this comparative example are completely consistent with those of Example 4. The difference is that furfurylamine is not added during the preparation of the crosslinking modifier, while the other raw material components, ratios and all preparation and curing process parameters are consistent with those of Example 4.

[0042] Comparative Example 5 The comparative example is completely consistent with the raw material dosage and preparation process of Example 1. The difference is that 1,4-butanediol diglycidyl ether is not added during the preparation of the crosslinking modifier. The other raw material components, ratios and all preparation and curing process parameters are consistent with those of Example 1.

[0043] (I) Curing residual internal stress test The residual internal stress of each group of samples after curing was tested using the thin film curvature method. Quartz-based optical waveguide chips of uniform specifications (20mm × 10mm, 0.5mm thickness, flatness ≤ 0.1μm) were selected. The front and back surfaces of the chips were evenly wiped with anhydrous ethanol, dried in an 80℃ oven for 15 minutes, and then cooled to room temperature in a dust-free desiccator. A quantitative coating of the adhesive was performed. 5g of the epoxy adhesive prepared in Examples 1-4 and Comparative Examples 1-5 was used and spin-coated at 3000r / min for 60s, controlling the coating thickness on the chip surface to be 120μm. After coating, segmented curing was completed. All cured composite samples were placed in a constant temperature and humidity environment (25℃, 50% relative humidity) for 24 hours. The thin film stress meter was preheated for 30 minutes. Test points were fixed for each group of samples, and the residual internal stress after curing was calculated using the following formula: In the formula: σ is the residual stress of the thin film; Es is the elastic modulus of the quartz substrate; ts is the substrate thickness; νs is the Poisson's ratio of the substrate; tf is the thickness of the encapsulation film; R is the radius of curvature of the substrate after coating; R0 is the radius of curvature of the substrate before coating.

[0044] (II) Mechanical property testing Referring to GB / T 2567-2008 "Test Methods for Performance of Resin Castings", a Type I dumbbell mold with precise and uniform cavity dimensions was used. 8g of epoxy resin from each group was vacuum degassed and injected uniformly into the mold. Cross-linking molding was completed according to the corresponding curing process for each group, and six parallel standard specimens were prepared for each group at once. All molded specimens were uniformly placed in a constant temperature and humidity curing chamber at 25℃ and 50% relative humidity for 24 hours to ensure complete stability of the internal cross-linking structure. The mechanical testing machine was preheated for 20 minutes, with a clamping distance of 60mm and a tensile testing rate of 2mm / min. Each group of specimens was clamped in the center of the fixture, and the tensile program was started uniformly until the specimen completely fractured. The ultimate tensile load and fracture deformation for each group were recorded. The tensile strength and fracture toughness were calculated using the following formulas: In the formula: σt is the tensile strength; Fmax is the maximum tensile load; b is the specimen width; d is the specimen thickness; KQ is the fracture toughness; S is the span.

[0045] (III) Optical transmission performance test Uniformly sized quartz-based planar waveguide optical splitter chips were selected. Each group was encapsulated with an equal amount of epoxy resin, with the encapsulation layer thickness precisely controlled at 120μm, completely covering the optical path area and fiber coupling interface. Five parallel devices under test (DUTs) were fabricated in each group. All DUTs were connected to an optical transmission test system, with test wavelengths set at 1310nm and 1550nm. The equipment was preheated for 30 minutes, and the optical path zero-point calibration was completed. Under normal temperature and pressure (25℃), the insertion loss and splitting uniformity of each group of devices were tested, and the initial quantization data for each group were recorded. All tested devices were placed in a high-low temperature cycling test chamber, and a standardized cycling program was set: -40℃ for 1 hour, followed by a temperature increase of 5℃ / min to 85℃ for 1 hour, constituting one cycle, and this cycle was continuously completed 50 times. After the cycle, the devices were removed and allowed to recover at 25℃ for 2 hours. The insertion loss and splitting uniformity were then retested under the same test wavelength and equipment parameters. The insertion loss and splitting uniformity of each group of devices were evaluated and calculated using the following formulas: In the formula: IL is the insertion loss; Pout is the output optical power; Pin is the input optical power; ΔIL is the beam splitting uniformity deviation; ILmax is the maximum insertion loss of each channel; ILmin is the minimum insertion loss of each channel.

[0046] The experimental results are shown in Table 1: Table 1. Experimental results of different embodiments and comparative examples

[0047] As shown in Table 1, the residual internal stress after curing in Examples 1-4 is generally at a low level, exhibiting superior tensile strength and fracture toughness. Furthermore, the insertion loss at room temperature, the insertion loss after high and low temperature cycling, and the deviation in spectroscopic uniformity are significantly better than those in the comparative examples. This indicates that the low-stress, detachable epoxy encapsulation material prepared by this invention possesses low-stress characteristics, excellent mechanical strength and toughness, and stable optical protection performance. This invention employs a rigid-flexible composite matrix composed of rigid and flexible epoxy resins, and introduces a self-synthesized dynamic crosslinking modifier. Within the system, a hybrid crosslinking network is constructed where permanent covalent bonds and thermally reversible dynamic covalent bonds coexist. The rigid resin skeleton provides stable mechanical support and structural strength, while the micro-conformation adjustment effect of flexible segments and dynamic bonds dissipates the residual stress generated by curing shrinkage, effectively solving the problem of traditional epoxy materials struggling to achieve both high strength and low stress. Simultaneously, a silane coupling agent improves the interfacial compatibility between the inorganic filler and the organic matrix, eliminates interfacial micro-defects, homogenizes the stress distribution of the system, and reduces stress concentration during the curing process. The stable and regular rigid-flexible hybrid cross-linked structure and low residual stress state can effectively avoid refractive index distortion and optical path coupling deviation in optical waveguide chips, suppress optical performance degradation under high and low temperature alternating conditions, and significantly improve the optical transmission accuracy and long-term service stability of planar waveguide optical splitters.

[0048] Comparative Example 1, which omitted the self-made crosslinking modifier, showed a significant increase in residual internal stress after curing, and a substantial decrease in tensile strength and fracture toughness. Its optical insertion loss and spectroscopic uniformity deviation at room temperature and after temperature changes were significantly worse than those of the Example. This is because the system only forms a single rigid permanent crosslinked network, lacking flexible buffer segments and dynamic stress-relieving structures. The curing volume shrinkage effect is significant, residual stress accumulates in large quantities, the overall brittleness of the material increases, and toughness is insufficient. The continuous internal stress easily compresses the optical waveguide chip and induces optical path distortion, ultimately leading to a significant decrease in mechanical properties and optical stability.

[0049] Comparative Example 2, without the addition of a silane coupling agent, exhibited higher residual stress and significantly weakened mechanical strength, toughness, and optical stability. This is because the inorganic filler and the epoxy organic matrix are only a simple physical blend, resulting in poor interfacial compatibility and numerous micropores and interfacial debonding defects. These defects easily induce localized stress concentration, compromising the mechanical structural integrity of the system. Furthermore, these interfacial defects continue to expand during high and low temperature cycling, disrupting the stability of the optical path coupling interface and leading to increased optical loss and accelerated performance degradation.

[0050] Comparative Example 3, which did not add 1,6-dimaleimide hexane during the preparation of the crosslinking modifier, exhibited the highest residual stress among all groups, and the most severe degradation in mechanical and optical properties. This is because a complete and effective crosslinking backbone could not be constructed, resulting in incomplete crosslinking reaction, a fragmented and loose crosslinking network, extremely uneven curing shrinkage, and disordered stress accumulation. Consequently, a stable structural support and optical path fixation effect could not be formed, leading to severe structural deformation during temperature changes and significantly compromising the stability of optical signal transmission.

[0051] Comparative Example 4, which did not include furfurylamine in the preparation of the crosslinking modifier, exhibited high residual stress, insufficient toughness, and significant fluctuations in optical parameters. This is because the system cannot generate thermally reversible DA dynamic covalent bonds; the crosslinking network retains only rigid permanent covalent bonds, lacking dynamic stress mitigation and microstructure adaptive adjustment capabilities. Consequently, it cannot effectively buffer curing shrinkage stress and alternating thermal stress, leading to long-term stress accumulation that disturbs the optical path structure, resulting in a significant decrease in spectral uniformity and optical stability.

[0052] The crosslinking modifier in Comparative Example 5 was not end-capped with a bifunctional epoxy diluent, resulting in a significant increase in residual stress, weakened fracture toughness, and lower optical stability compared to the examples. This is because the reactivity of the modifier cannot be controlled, leading to a violent and disordered crosslinking reaction, excessively high crosslinking density, overly tight molecular chain packing, increased curing volume shrinkage, increased material brittleness, decreased resistance to deformation, and the tendency of internal residual stress to induce microscopic defects, causing fluctuations in optical path parameters and deteriorating the optical performance stability of the device.

[0053] In summary, this invention constructs a composite matrix by combining rigid and flexible epoxy resins, and uses self-synthesized dynamic crosslinking modifiers and silane coupling agents for interface modification to build a stable hybrid crosslinking network, effectively balancing the material's low stress and high strength and toughness, and significantly reducing curing residual stress and optical loss.

[0054] In the description of this specification, the reference to terms such as "embodiment," "various embodiments," etc., indicates that a specific feature, structure, material, or characteristic described in connection with that embodiment or preparation example is included in at least one embodiment of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments.

[0055] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A low-stress, removable epoxy encapsulation material, characterized in that, The raw material components, by weight, include: 60-70 parts epoxy resin, 25-35 parts crosslinking modifier, 3-6 parts filler, 1.5-3.0 parts antioxidant, and 0.5-1.0 parts silane coupling agent; The crosslinking modifier is specifically prepared through the following steps: S1. Melt 1,6-dimaleimide hexane, add furfurylamine dropwise, and continue the reaction at the same temperature after the dropwise addition is completed to obtain the prepolymer melt; S2. Cool the prepolymer melt, then add a bifunctional epoxy diluent for end-capping, and control the reaction system conditions to obtain the crosslinking modifier. In step S1, the melting temperature is 130-140℃, the dropping rate of furfurylamine is 1-2 drops per second, the dropping process lasts for 45-60 minutes, and the stirring is continuous during the dropping process; after the dropping is completed, the reaction is continued at this temperature range for 2.0-3.0 hours, and the entire reaction is carried out under the protection of inert gas; The mass ratio of 1,6-dimaleimide hexane to furfurylamine is 1:(1.30-1.59). After the prepolymer melt is cooled to 65-75℃, a bifunctional epoxy diluent is added.

2. The low-stress, removable epoxy encapsulation material according to claim 1, characterized in that, The epoxy resin is composed of flexible epoxy resin and rigid epoxy resin, with a mass ratio of (1-2):

1. The flexible epoxy resin is selected from one or more of polypropylene glycol diglycidyl ether, butylene glycol diglycidyl ether, and neopentyl glycol diglycidyl ether; The rigid epoxy resin is selected from one or more of bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, and o-cresol epoxy resin.

3. The low-stress, removable epoxy encapsulation material according to claim 1, characterized in that, The filler is selected from one or more of silica, alumina, and boron nitride, and the particle size of the filler is 0.5-10μm.

4. The low-stress, removable epoxy encapsulation material according to claim 1, characterized in that, The antioxidant is selected from one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene.

5. The low-stress, removable epoxy encapsulation material according to claim 1, characterized in that, The silane coupling agent is selected from one or more of γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

6. The low-stress, removable epoxy encapsulation material according to claim 1, characterized in that, In step S2, the bifunctional epoxy diluent is selected from one or more of neopentyl glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, and polyethylene glycol diglycidyl ether, and its addition amount is 5-15% of the mass of 1,6-dimaleimide hexane.

7. The low-stress, removable epoxy encapsulation material according to claim 1, characterized in that, Step S2 also includes adding a catalyst, which is selected from one or more of benzyl dimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 2-methylimidazole, and the amount added is 0.05-0.2% of the melt weight of the prepolymer.

8. The low-stress, removable epoxy encapsulation material according to claim 1, characterized in that, It is prepared by the following steps: The epoxy resin, filler, and silane coupling agent are mixed evenly at 80-100℃ and then subjected to vacuum degassing. Subsequently, a crosslinking modifier heated to 60-70℃ is added and blended to form a homogeneous adhesive solution. This solution is then injected into a preheated mold and subjected to pre-curing at 80℃, curing at 100℃, and post-curing at 120℃ to complete the crosslinking process. After cooling, the product is obtained.

9. A planar waveguide optical splitter, characterized in that, It includes an optical waveguide chip and a packaging layer covering the optical waveguide chip, wherein the packaging layer is made of a low-stress removable epoxy packaging material as described in any one of claims 1-8.

Citation Information

Patent Citations

  • Composite epoxy type electron packaging material and preparation method thereof

    CN101054508A

  • Curable resin composition and dry film

    JP2025059604A